A comparative study of honey-betadine dressing and paraffin gauze dressing on skin graft donor site - Voorakalli, Bhargavi V.; Kushagra, Luv; Suraj, Lisha (International Journal of Research in Medical Sciences, 2026)
Background: Honey has long been used in Indian medicine for its anti-inflammatory, antibacterial and wound-healing properties. Split-thickness skin grafting is a common reconstructive method in surgery, yet there is no universally accepted, standardized dressing for donor sites that is simple, affordable and effective. This study evaluates honey as a donor site dressing to establish scientific evidence for its benefits. Methods: A prospective randomized controlled trial was conducted at MGM Hospital, Navi Mumbai, from April 2025 to September 2025. Postoperative patients undergoing split-thickness skin grafting for healed ulcers were allocated into two groups: honey–betadine dressing or paraffin gauze dressing at the donor site. Results: In the honey–betadine group, complete epithelialization occurred in 60% by day 7, 26.6% by day 10 and 6.6% by day 14. In contrast, only 33.3% of the paraffin gauze group healed by day 10, with 73.3% achieving complete healing by day 14 or later. Pain assessment revealed that in the honey–betadine group, 73.3% reported only mild or moderate pain, compared with 26.6% in the paraffin gauze group, where higher proportions experienced severe or very severe pain. Conclusions: An ideal donor site dressing should be readily available, cost-effective, hydrating, antibacterial, infection-preventive, and promote rapid healing with minimal discomfort. Honey fulfils these criteria, demonstrating faster epithelialization, better pain outcomes and improved patient comfort compared with paraffin gauze.